Pendampingan Penyusunan Profil Negeri Melalui Kuliah Kerja Nyata Tematik di Negeri Soahuku Kabupaten Maluku Tengah - Luturkey, William; Rasyid, Risal; Aswad, Wa Ode Sitti Jurianti; Kesaulya, Hertine Megiestri (EMPOWERMENT: Journal of Community Practice, 2024)
Village government is the spearhead that is directly related to the community in real life. The process of village planning, and development needs basic data that includes an overview of the area, government, human resources, facilities, and infrastructure and the potential that the village has, but in its implementation, it is still very difficult to realize. The method used in Community Service Activities through Thematic KKN in Soahuku Village, Amahai District, Central Maluku Regency is a descriptive method. Data collection techniques through observation, interviews, and documentation by carrying out several stages ranging from planning, program implementation to publication of the latest and more informative Soahuku Village Profile data presented in a book and x-banner. The results of the analysis show that the need for basic data that includes an overview of the region, Government, Human Resources, Facilities, and Infrastructure and Potential owned by the Village Village which is summarized more informatively in a profile book of the Soahuku Village is considered quite important to be used as a guideline for the planning and development process of the Soahuku Village.